An Exploratory Study on Implementation of Online Learning by Students During the COVID-19 Pandemic - Wahyu Nugroho; Elma Rosalia Malinda; Maulika Junia Mustika Rani; Basori Basori (Pancaran Pendidikan, 2020)
COVID-19 was announced as a pandemic. Indonesia has been applying online learning as an attempt to break the COVID-19 spread-chain. The purpose of this study was to identify the implementation of online learning by students during the COVID-19 pandemic. The research used qualitative research with a literature study method. Data analysis was performed by triangulating data sources. Based on the results of an analysis of the implementation online learning at university level, it is known that there are students who strongly support the implementation of online learning and students who do not have enthusiasm for online learning. Student enthusiasm is influenced by technical and non-technical factors which some aspects can become an obstacle. Several solutions can be done to solve the weakness of online learning. Implementation of online learning still has advantages and disadvantages that should be able to be evaluated by the government.